1955
DOI: 10.1039/jr9550002807
|View full text |Cite
|
Sign up to set email alerts
|

Studies in the synthesis of cortisone. Part XII. Improvements in the conversion of sapogenins into pregnan-20-ones

Abstract: The conversion of steroidal sapogenins (I) into pregnan-20-ones (VI) by way of the 4-sapogenins (11) is improved, particularly for 1 l-oxotigogenin and its esters (Ic). In the first step furost-22-ens are evidently formed as well as the desired 4-sapogenins, but this difficulty and others are avoided by methods described.THE development of practicable means of making ll-oxotigogenin and its esters (Ic) from hecogenin (Ib; R = H) (Schmidlin and Wettstein, Helv. Chim. Acta, 1953Acta, , 36, 1241 Cornforth, Osbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1961
1961
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Gould et al [9] observed that the conversion could be achieved at the boiling point of acetic anhydride in the presence of acetyl chloride or anhydrous AlCl 3. Similar conditions using acetyl chloride also have been used for the transformation of ∆ 4,6 -22-isospirostadiene-3-one to the corresponding 3b-acetoxy-3,5,7-triene [11].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Gould et al [9] observed that the conversion could be achieved at the boiling point of acetic anhydride in the presence of acetyl chloride or anhydrous AlCl 3. Similar conditions using acetyl chloride also have been used for the transformation of ∆ 4,6 -22-isospirostadiene-3-one to the corresponding 3b-acetoxy-3,5,7-triene [11].…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards several modifications have been made including catalytic conversion to effect this isomerization process [9][10][11][12][13]. Gould et al [9] observed that the conversion could be achieved at the boiling point of acetic anhydride in the presence of acetyl chloride or anhydrous AlCl 3.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations